2020
DOI: 10.3168/jds.2020-18357
|View full text |Cite
|
Sign up to set email alerts
|

Effects of milk proteins and posttranslational modifications on noncoagulating milk from Swedish Red dairy cattle

Abstract: Milk that does not coagulate after rennet addition, also called noncoagulating (NC) milk, is unwanted in cheese production due to prolonged processing time. Amounts of whey and casein proteins, genetic variants, as well as posttranslational modifications (PTM) of proteins are all contributing factors in rennet-induced coagulation of milk. In this study, we conducted a wideranging investigation of milk proteins in milk samples from 616 Swedish Red dairy cattle using liquid chromatography-high resolution mass sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 42 publications
3
22
0
Order By: Relevance
“…The κ-casein concentration and its proportion in relation to α S1 -and β-caseins were reported to be low in poorly coagulating and noncoagulating BM (Wedholm et al, 2006). It was recently reported that the noncoagulating property of milk from red cattle significantly correlated with higher relative concentrations of α-LA and β-casein and lower relative concentrations of β-LG and κ-casein (Nilsson et al, 2020). The anticoagulation properties of β-casein can be explained by its chaperone-like activity (Zhang et al, 2005).…”
Section: Short Communication: Caseins and α-Lactalbumin Content Of Camel Milk (Camelus Dromedarius) Determined By Capillary Electrophoresmentioning
confidence: 99%
“…The κ-casein concentration and its proportion in relation to α S1 -and β-caseins were reported to be low in poorly coagulating and noncoagulating BM (Wedholm et al, 2006). It was recently reported that the noncoagulating property of milk from red cattle significantly correlated with higher relative concentrations of α-LA and β-casein and lower relative concentrations of β-LG and κ-casein (Nilsson et al, 2020). The anticoagulation properties of β-casein can be explained by its chaperone-like activity (Zhang et al, 2005).…”
Section: Short Communication: Caseins and α-Lactalbumin Content Of Camel Milk (Camelus Dromedarius) Determined By Capillary Electrophoresmentioning
confidence: 99%
“…The isoforms identified in these stud-ies covered 1 and 2P (phosphorylated) molecular forms, in combination with 0-3G (glycosylated) patterns, even in milk at the individual cow level. Specifically, a few of the individual cow milk samples were found to contain low abundant 0P or even 3P forms (Nilsson et al, 2020), though detailed PTM profiles for each variant were not shown. Therefore, it is now revealed to which extent the 3 different variants A, B, and E present with different isoform patterns, in different amounts, or both.…”
Section: Introductionmentioning
confidence: 98%
“…By liquid chromatography coupled to electrospray mass spectrometry (LC-ESI/MS), either by analysis of caseinomacropeptide (CMP) released from κ-CN variants A, B, or E (Jensen et al, 2015;Sunds et al, 2019) or the intact κ-CN molecule (Miranda et al, 2020;Nilsson et al, 2020), isoforms of κ-CN in milk were investigated. The isoforms identified in these stud-ies covered 1 and 2P (phosphorylated) molecular forms, in combination with 0-3G (glycosylated) patterns, even in milk at the individual cow level.…”
Section: Introductionmentioning
confidence: 99%
“…The average degree of κ-CN glycosylation among breeds was 46 ± 12%, with highest glycosylation of genetic Variant B. Jensen et al [30] reported levels of 34-36% including all genetic variants in Danish Jersey and Danish Holstein milk based on 2D gels, and slightly more glycosylation could also be ascribed to genetic Variant B. The most dominating glycosylated isoforms ᴋ-CN 1P (e) and ᴋ-CN 1P (e, e), which have been confirmed by other studies on milk from Swedish Red, Holstein, Normande and Montbéliarde cattle [38,39]. The triple glycosylated isoform ᴋ-CN 1P (b, c/d, e) was highly prevalent in genetic Variant A compared to Variant B for the breeds Western Finncattle, Eastern Finncattle, native Lithuanian Black and White, Danish Red anno 1970 and Norwegian Telemark cattle.…”
Section: Post-translational Modifications Of κ-Casein Among Native Breedsmentioning
confidence: 65%
“…Further, the present study identified four breeds that expressed tri-phosphorylated ᴋ-CN. A limited number of tri-phosphorylated ᴋ-CN isoforms have previously been identified in samples from Danish Holstein [26] and Swedish Red [38].…”
Section: Post-translational Modifications Of κ-Casein Among Native Breedsmentioning
confidence: 99%